2019
DOI: 10.1101/555318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional enhancer elements drive subclass-selective expression from mouse to primate neocortex

Abstract: Myriad cell types comprise the human neocortex, but their roles in normal brain function and disease are largely unknown because few tools exist. To find enhancer elements useful for cell type-specific genetic tools, we examined chromatin accessibility in >2,800 highquality single human neocortical nuclei. Accessible elements frequently are conserved in mouse distributing tissue.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…In order to determine the fidelity of organoids as a model for the epigenomic landscape of the developing brain, functional characterization of conserved and non-conserved chromatin features in vivo and in vitro will be required. In addition to serving as a reference for evaluating in vitro models of human brain development, our data will enable scalable prediction of candidate cell type specific regulatory elements that could facilitate the development of enhancer-based tools for accessing molecularly-defined cell types [57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the fidelity of organoids as a model for the epigenomic landscape of the developing brain, functional characterization of conserved and non-conserved chromatin features in vivo and in vitro will be required. In addition to serving as a reference for evaluating in vitro models of human brain development, our data will enable scalable prediction of candidate cell type specific regulatory elements that could facilitate the development of enhancer-based tools for accessing molecularly-defined cell types [57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the difficulty in targeting diverse interneuron subclasses, we performed rapid viral genetic labeling of cortical GABAergic interneurons. We applied an adeno-associated virus (AAV) vector that drives SYFP2 reporter express under the control of an optimized forebrain GABAergic neuron enhancer (Stuhmer et al, 2002; Dimidschstein et al, 2016) in human organotypic slice culture (see Methods ; Ting et al, 2018; Mich et al, 2020). Inhibitory subclass identity was established post-hoc by mFISH staining.…”
Section: Resultsmentioning
confidence: 99%
“…We showed that this methodological approach of quadruple modality functional characterization can be extended to slice culture with viral labeling as well. This approach is well poised to take advantage of an increasing number of enhancer-driven subclass and type-specific viral tools (Dimidschstein et al, 2016; Hrvatin et al, 2019; Jüttner et al, 2019; Mehta et al, 2019; Nair et al, 2019; Mich et al, 2020; Graybuck et al, 2020; Vormstein-Schneider et al, 2020) to allow prospective targeting of cell classes or subclasses, and subsequent refinement of cell type identity by a combination of marker genes using mFISH. Brain slice culturing and viral transgenesis will allow not only measurement, but also functional manipulation of the human microcircuit, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of these studies, single-cell ATAC-Seq paired with single-cell RNAseq was employed in order to detect which GREs are active in each cluster identified. They created AAVs with the selected GREs driving expression of recombinases or fluorescent proteins and validated their expression [358], [359].…”
mentioning
confidence: 99%